Environmental communication for the rice field conservation in Semende Darat Tengah, South Sumatra - Yenrizal Yenrizal (Universitas Padjadjaran, 2021)
Depreciation of paddy fields has become a common phenomenon due to the conversion of land functions from agriculture to non-agriculture. The reasons are due to economic factors, settlement development, or policy. In the Semende Darat Tengah of South Sumatra, the paddy fields remain, and even the areas are expanding. This study aims to identify and understand how environmental communication mechanisms are applied in local communities, especially in Semende Darat Tengah, South Sumatra, to preserve the existence of rice fields. Methodologically, this study was conducted through communication ethnography. The authors live and interact with the community and research environment. Data analysis is carried out during the research process by combining the ethical elements of the study. This study indicates that the ongoing environmental communication mechanism is based on knowledge and understanding of the prevailing customary order and knowledge of local physical conditions. This knowledge undergoes an internalization that occurs continuously, from the ancestor eras, since the settlement was formed. The internalization process can be seen from listening, comprehending, and performing activities that become a shared perception of the rice fields and the local environment. This internalization takes place in a variety of natural environmental communication settings. The three main aspects that build people’s perceptions are knowledge of the nuclear family level, interactions with neighbors and other communities, and the preserved traditional institutions.